The Periscreen Strip Is Highly Efficient for the Exclusion of Spontaneous Bacterial Peritonitis in Cirrhotic Outpatients. (October 2016) - Thévenot, Thierry; Briot, Charline; Macé, Vincent; Lison, Hortensia; Elkrief, Laure; Heurgué‐Berlot, Alexandra; Bureau, Christophe; Jézéquel, Caroline; Riachi, Ghassan; Louvet, Alexandre; Pauwels, Arnaud; Ollivier‐Hourmand, Isabelle; et al.
Abstract : Objectives: We aimed to assess the performance of a new strip (Periscreen) for the rapid diagnosis of spontaneous bacterial peritonitis (SBP). Methods: Ascitic fluid (AF) of cirrhotic patients hospitalized between March 2014 and August 2015 was independently tested by two readers using the new strip, which has four colorimetric graduations (negative, trace, small, and large). SBP was diagnosed on neutrophils in ascites>250/mm 3 . Ascites not related to portal hypertension were excluded. Results: Overall, 649 patients from 21 French centers were included and 1, 402 AF (803 AF samples from 315 outpatients and 599 samples from 334 inpatients) were assessed. Eighty‐four AF samples (17 AF in 9 outpatients and 67 AF in 31 inpatients) were diagnosed as SBP. The prevalence of SBP was 6% (2.1% in outpatients vs. 11.2% in inpatients; P <0.001) and 7.2% in patients with symptoms suggestive of SBP (3% in outpatients vs. 11.3% in inpatients; P <0.001). The κ value for inter‐reader agreement was 0.81 (95% confidence interval: 0.77–0.84) when using the "trace" threshold. Considering discordant results ( n =131) as positive to interpret the diagnostic performance of the strip at the "trace" threshold, sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were 91.7, 57.1, 12.0, and 99.1%, respectively. At this "trace" threshold, sensitivity and NPV were both 100% in outpatients, and 89.5 and 97.9% in inpatients, respectively. At the "small" threshold, sensitivity, specificity, PPV and NPV were 81.0, 85.9, 25.9 and 98.7%, respectively. Conclusions: The Periscreen strip is a rapid and highly efficient tool for excluding SBP in the outpatient setting.